Digital Service Model of Red Educational Resources from the Perspective of Excellent Traditional Culture - Dan Liu (Discrete Dynamics in Nature and Society)
In view of the poor service effect caused by the incomplete index base of the traditional red education resources digital service model, this paper puts forward the red education resources digital service model from the perspective of excellent traditional culture. Determine the influencing factors of red education resources in the integration process, integrate the remote scheduling principle of teaching information into the feature vector extraction of red education resources, extract the number of main factors of the feature vector, decompose the feature vector of red education resources, take the wavelet entropy of red education resources as the fusion weight, and integrate the obtained coefficients through wavelet transformation. Get the integration results of red education resources. Build the architecture of digital service model, grab all web pages on the Internet with indexer, and create forward index and reverse index. Use the controller to search web pages and control all web pages to be searched. Restrict query conditions through user interface. Establish a red education resource data index database, query and process documents, and build a digital service model. The experimental results show that the designed service model has good goodness of fit and high performance.